Assessment of urban park landscape setting design towards carbon sequestration rate - Othman, Rashidi; Mohd Noor, Nur Fadhlina; Hashim, Khairusy Syakirin Has-Yun; Mohd. Yaman, Maheran; Abdullah, Fadzidah; Suid, Suhaili (Medwell, 2016)
Urban parks varies in size ranging from 400 to 30 000 hectares all over the world and one thing in common they possessed is that urban trees play an important role in mitigating the impacts of climate change by sequestering atmospheric carbon dioxide (CO2). Calculation of carbon (C) stored and sequestered by urban trees is the actual and critical assessment of the real potential role of an urban park in reducing atmospheric CO2. This paper provides a case study of the quantification of C storage and sequestration by two urban parks with two different landscape setting design in Subang Jaya and Damansara, a rapidly urbanized and populated city in west coast of Malaysia. The C storage or sequestration rate was estimated by biomass equations, using field inventory and analysis survey data. The calculation of biomass provides reasonably accurate estimation of the amount of carbon that was sequestered from trees over the years. Our findings revealed that different landscape setting design contribute to marked differences in carbon stored. Curvilinear landscape setting design was found to sequester more carbon compared to informal landscape setting even though total green and built up areas for both sites are similar. These findings provide insights and better understanding of the role of urban park as carbon sink.